Sampling Methods in Clinical Research; an Educational Review - Elfil, Mohamed; Negida, Ahmed (Archives of Academic Emergency Medicine, 2017)
Clinical research usually involves patients with a certain disease or a condition. The generalizability of clinical research findings is based on multiple factors related to the internal and external validity of the research methods. The main methodological issue that influences the generalizability of clinical research findings is the sampling method. In this educational article, we are explaining the different sampling methods in clinical research.